2013
DOI: 10.1007/978-3-642-36973-5_1
|View full text |Cite
|
Sign up to set email alerts
|

Using Intent Information to Model User Behavior in Diversified Search

Abstract: A result page of a modern commercial search engine often contains documents of different types targeted to satisfy different user intents (news, blogs, multimedia). When evaluating system performance and making design decisions we need to better understand user behavior on such result pages. To address this problem various click models have previously been proposed. In this paper we focus on result pages containing fresh results and propose a way to model user intent distribution and bias due to different docu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…These include the personalized click model [30], the task-centric click model [37], intent-aware modifications of UBM and DBN [9], the federated click models [6], the vertical-aware click model [33], the content-aware click model [34], and noise-aware modifications of UBM and DBN [7].…”
Section: Click Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…These include the personalized click model [30], the task-centric click model [37], intent-aware modifications of UBM and DBN [9], the federated click models [6], the vertical-aware click model [33], the content-aware click model [34], and noise-aware modifications of UBM and DBN [7].…”
Section: Click Modelsmentioning
confidence: 99%
“…Figure 6 plots the t-SNE projections of the vector state s7 for different distances to the previous click. 9 Here, we compute the vector states for the query sessions in Sa, and then filter out some vector states to construct a balanced set that contains equal number of vector states for each distance d = 0, 1, . .…”
Section: Concepts Learned By Ncmmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that patterns of user click behaviour can be learned automatically from interaction data [6]. In addition to position bias, recent work examines other types of bias including(i) vertical bias driven by visually salient vertical results (e.g., image results, video results, news results) [11,12,43]; (ii) query bias, which occurs if a query does not match the user's information need [45], (iii) duplicate bias, which occurs if a result has been examined earlier in the search task [45]; and (iv) bias driven by individual differences between users [40].…”
Section: Models Of User Behaviormentioning
confidence: 99%
“…I will highlight progress on the interface of these areas by focusing on three examples. In the first, I focus on result pages containing fresh results and propose a way to model user intent distribution and bias due to different document presentation types [1]. In the second, I focus on the fresh vertical prediction task for repeating queries and address the following algorithmic problem: how to quickly and accurately detect fresh intent shifts and adjust the ranking in an online setting [3].…”
Section: Recent Advancesmentioning
confidence: 99%